A imagem em movimento e o espaço-tempo : Bill Viola em meditações - Arçari, André Nascimento (2018)
This dissertation encompasses, in the internal, philosophical and emotional dimension, the relations between space and time — or as often punctuated, space-time — as constitutive elements of artworks, as well as seeking to investigate certain problematics